2018
DOI: 10.1088/1361-6560/aad3ae
|View full text |Cite
|
Sign up to set email alerts
|

Validating a Monte Carlo approach to absolute dose quality assurance for proton pencil beam scanning

Abstract: For radiotherapy, it is crucial to guarantee that the delivered dose matches the planned dose. Therefore, patient specific quality assurance (QA) of absolute dose distributions is necessary. Here, we investigate the potential of replacing patient specific QA for pencil beam scanned proton therapy with Monte Carlo simulations. First, the set-up of the automated Monte Carlo model is presented with an emphasis on the absolute dose validation. Second, the absolute dose results obtained from the Monte Carlo simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 32 publications
3
43
0
Order By: Relevance
“…As for fast planning and plan QA, we have previously demonstrated that the complete optimization of plans can be performed in just a few seconds [13], whereas efficient independent dose calculations, based on machine control files, provided a fast and sensitive alternative to plan specific QA measurements [14,33]. Finally, although accurate contour propagation and dose accumulation for deformable geometries are still challenging [34], for the paranasal sinuses spatial transformations between daily datasets are predominantly rigid, simplifying both processes considerably.…”
Section: Patientmentioning
confidence: 99%
“…As for fast planning and plan QA, we have previously demonstrated that the complete optimization of plans can be performed in just a few seconds [13], whereas efficient independent dose calculations, based on machine control files, provided a fast and sensitive alternative to plan specific QA measurements [14,33]. Finally, although accurate contour propagation and dose accumulation for deformable geometries are still challenging [34], for the paranasal sinuses spatial transformations between daily datasets are predominantly rigid, simplifying both processes considerably.…”
Section: Patientmentioning
confidence: 99%
“…In contrast however, for PBS proton therapy, even though there is a low-dose spray due to interactions within the beam line and Gantry, 19,22 MC simulations can be started at a defined point before the patient, and not all hardware needs to be explicitly modelled. [17][18][19][20][21] At this starting point, each pencil beam is described by its number of protons, energy, energy spread, and initial optical phase space (beam size, angular spread and correlation). In this study, proton numbers per monitor units have been defined based on Faraday cup measurements (see Winterhalter et al 17 for more details on the absolute dose validation of this approach), nominal energy and energy spreads have been iteratively adjusted to reproduce depth-dose curves in water and the initial optical phase space characterised by subtracting the air scattering contribution from the measured beam data (see Grevillot et al 20 for more detail).…”
Section: Beam Modelling For a Pbs MC Systemmentioning
confidence: 99%
“…[17][18][19][20][21] At this starting point, each pencil beam is described by its number of protons, energy, energy spread, and initial optical phase space (beam size, angular spread and correlation). In this study, proton numbers per monitor units have been defined based on Faraday cup measurements (see Winterhalter et al 17 for more details on the absolute dose validation of this approach), nominal energy and energy spreads have been iteratively adjusted to reproduce depth-dose curves in water and the initial optical phase space characterised by subtracting the air scattering contribution from the measured beam data (see Grevillot et al 20 for more detail). Additionally, to deliver pencil beams with energies below the lowest range that can be transported through the beam line (70 MeV for the PSI Gantry 2), a pre-absorber (range shifter) is typically required.…”
Section: Beam Modelling For a Pbs MC Systemmentioning
confidence: 99%
See 2 more Smart Citations